Association between Emotional Intelligence and Hemispheric Activity Asymmetry - Razumnikova, O; Khoroshavtseva, E; Yashanina, A (KnE Life Sciences, 2018)
The relations between the asymmetry of hemispheric activity using the EEG rhythms in resting and both trait emotional intelligence (EI-IPIP) and self-assessment of emotional reactivity on IAPS stimuli were studied in university students. The obtained EEG patterns of power asymmetry in both low-frequency and high-frequency indicate different variants of the hemispheric dominance in the anterior and posterior regions of the brain, depending not only on the valence of induced emotions, but also on selfassessment of perception or expression of emotional states. Total EI was associated with relatively greater left frontal activation on low frequency delta oscillations and on higher beta2 oscillations in posterior cortex. Using EEG mapping positive relations were found between the right hemispheric delta rhythm and emotional reactivity to negative emotive stimuli and between the left hemispheric delta and positive affect. Self-rating of positive to negative emotion during both EI and IAPS stimuli-induced affect testing was more pronounced in the relationships to asymmetry of hemispheric activity than separate traits EI. Keywords: Emotional intelligence traits, self-assessment of emotional reactivity, EEG, hemispheric asymmetry, frequency bands